Perbedaan Kompres Bawang Merah dan Tepid Sponge terhadap Penurunan Suhu Tubuh pada Balita Demam di Wilayah Kerja Puskesmas Kedungmundu Semarang - Puput Kurnia Sari; Rohmatun Rohmatun; Muhamad Syarifudin; Irene Fernandes (Fakultas Ilmu Kesehatan, 2023)
Fever in children is a condition that often causes anxiety, so mothers often givefebrifuge when their child has a fever. This is done by parents because feverreducing drugs, both those obtained with a doctor's prescription, and thosethat are sold freely in stalls, are considered to be able to make a child's healthcondition better in a relatively short time. Objective: To prove the differencethe effectiveness of giving shallot compresses and tepid sponges on decreasingbody temperature in toddlers who have fever in the Kedungmundu HealthCenter Semarang Work area. Research Method: using a Quantitative a quasiexperimentalmethod using a Quasi Experiment research design with a pretes and post-test two group design.The sample is 34 people with Purposive Sampling technique. Test the normality of the data with the Shapiro wilk test, parametric test Paired sample t test Wilcoxon non-parametric test. Result: The results showed that in the tepid sponge group the average temperature decrease of 0.976oC (S.D ± 0.3270) whereas in the onion compress group red the average temperature decrease was 1.106oC (S.D ± 0.3699). The difference in the average decrease the temperature between the two groups was 0.1294oC (95% CI -0.3733 – 0.1145). T test results no in pairs obtained a significance value of 0.288 (ρ > 0.05) and Conclusion is that there is no difference in the effectiveness of lowering body temperature in toddlers with fever after giving the shallot intervention and in the group with the tepid sponge intervention. There was no significant difference in mean temperature difference between the tepid sponge group and the shallot compress group, but the red onion compress reached normal temperature faster than the tepid sponge